An analysis of the German university admissions system - Alexander Westkamp (University of Bonn, Bonn Graduate School of Economics (BGSE), 2012)
This paper analyzes the sequential admissions procedure for medical subjects at public universities in Germany. Complete information equilibrium outcomes are shown to be characterized by a stability condition that is adapted to the institutional constraints of the German system. I introduce matching problems with complex constraints and the notion of procedural stability. Two simple assumptions guarantee existence of a student optimal procedurally stable matching mechanism that is strategyproof for students. n the context of the German admissions problem, this mechanism weakly Pareto dominates all equilibrium outcomes of the currently employed procedure. Applications to school choice with affirmative action are also discussed.
Keywords: C78; D02; 330; University Admissions; Matching; Stability; Strategyproofness; Complex Constraints